Cinnamomum verum-derived bioactives-functionalized gold nanoparticles for prevention of obesity through gut microbiota reshaping. (January 2022) - Sharma, Vivek K.; Prateeksha,; Gupta, Sateesh C.; Singh, Brahma N.; Rao, Chandana V.; Barik, Saroj K.
Abstract: Existing drugs have limited success in managing obesity in human due to their low efficacy and severe side-effects. Surface-modified gold nanoparticles have now received considerable attention of researchers for efficient biomedical applications owing to their superior uptake by cells, biocompatibility, hydrophilicity and non-immunogenicity. Here we prepared Cinnamomum verum derived bioactives-functionalized gold nanoparticles (Au@P-NPs) and assessed their impact on obesity and related immune-metabolic complications in high-fat diet (HFD)-induced obese mice using metabolic experiments along with 16S RNA gene-based gut microbial profiling and faecal microbiota transplantation (FMT). Au@P-NPs treatment prevented weight gain, decreased fat deposition, reduced metabolic inflammation and endotoxaemia in HFD-fed mice. Au@P-NPs-treated group exhibited better glucose tolerance and insulin sensitivity than HFD-fed control mice, and got completely protected against hepatic steatosis. These impacts were related to increased energy expenditure and enhanced Ucp1 expression in the brown adipose tissues of Au@P-NPs-administered animals, which strongly linked with the mRNA expression of the membrane bile acid receptor TGR5. Treatment of HFD-fed animals with Au@P-NPs altered plasma bile acid profile, and increased Akkermansia muciniphila and decreased Lactobacillus populations in the faeces. Au@P-NPs-treated animals revealed altered plasma bile acid profile, and increased Akkermansia muciniphila and decreased Lactobacillus populations in the faeces. FMT experiments showed lesser weight gain and greater energy expenditure in the mice fed with faecal suspension from Au@P-NPs-treated animals than that from HFD-fed mice. These results clearly establish that gold nanoparticles functionalized with bioactive compounds of C. verum have high potential to be an anti-obesity drug. Graphical abstract: Image 1